Free-living clinging flatworms (Rhabditophora, Polycladida) associated with Sargassum from the Caribbean Coast of Colombia - Jorge Merchán Mayorga; Sigmer Quiroga; Isabella Posada; Katherin García-Ramos (Biodiversity Data Journal)
Polyclads are a diverse group of marine free-living flatworms, with some species adapted to life in floating Sargassum mats. Recent studies suggest that, rather than being inherently pelagic, these flatworms should be classified as "clinging fauna", as they rely on floating substrates for habitat.This study documents, for the first time, the occurrence of Gnesioceros sargassicola and Chatziplana grubei in Sargassum along the Caribbean coast of Colombia. High-definition photographs of whole mounts and histological sections are provided for both species, along with detailed observations of their reproductive structures and 28S rDNA barcodes. These findings underscore the importance of exploring the fauna associated with Sargassum, contributing to a better understanding of polyclad distribution and raising the number of recorded species for Colombia to 26.